Influence of Zn-Nb on the magnetic properties of barium hexaferrite - Kanagesan, Samikannu; Hashim, Mansor; Jesurani, Sinnappan; Thirunavukarasu, Kalaivani; Ismail, Ismayadi (Springer, 2014)
In the present study, BaFe12-2x Zn x Nb x O19 (x=0. 2, 0.4, 0.6 and 0.8) hexaferrites were prepared by the sol-gel technique and subsequent thermal treatment. The crystal structure, grain size, and magnetic properties were studied by means of X-ray diffraction (XRD), high-resolution scanning electron microscope (HR-SEM) and vibrating sample magnetometer (VSM). The X-ray diffraction analysis showed that the barium hexaferrite with small substitutions still maintained a hexagonal magneto-plumbite phase. It was found that the mean size of the grains increased with increasing substitution. The saturation magnetization increased slightly with increasing x, which was attributed to different preferential site occupation of Zn-Nb at low and high concentration ranges. The coercivity decreased with increasing x. Structural and magnetic characterizations of these ferrites provide significant information about their reactive physical properties.